Climate change drives glacier retreat in Bhaga basin located in Himachal Pradesh, India. Issue 11 (17th August 2020) - Kaushik, Saurabh; Dharpure, Jaydeo K.; Joshi, P.K.; Ramanathan, AL; Singh, Tejpal
Abstract: This paper reports changes in different glaciers of Bhaga basin located in western Himalaya, from 1979 to 2017. Glacier boundaries were delineated through semi-automated approach using Landsat satellite imagery. The variation of glacier extent in different elevation zones, snout retreat and decadal changes are observed. Results show that the total area of glaciers was 238  km 2 in 1979, which reduced to 230.8  km 2 by 2017 (retreat rate 12 m  yr − 1 ). Glaciers at low elevation and smaller in size are retreating faster. Analysis of Asian Precipitation-Highly Resolved Observational Data Integration Towards Evaluation data shows decreasing trend of annual precipitation (–2.724  mm  yr − 1, 1951–2015 ) and increasing trend of mean annual temperature (0.021 °   C  yr − 1 ). The statistical analysis using Mann-Kendall and Sen's slope tests, applied at different confidence interval demonstrates that climate change corresponds to deglaciation, and topography controls glacier recession in the basin.